Waiting for the national broadband network: Challenges of connectivity in regional Australia - Catherine Middleton; Sora Park (International Telecommunications Society (ITS), 2014)
There is enormous demand for high quality, reliable broadband service in regional Australia. But despite years of planning and promises, significant action to improve access to broadband services has not yet taken place in regional Australia. In fact, following a 2013 change in the federal government, there is now greater uncertainty as to the nature and timing of investment as the government-owned National Broadband Network company (NBN Co) is reviewing its approach and rollout schedule. This paper explores the need for better broadband in regional Australia and outlines the failure of the NBN to deliver improvements in a timely way. It notes that the prospects for immediate improvements in broadband availability in regional Australia are not good. Actions to reduce the politicization of broadband development and to diminish uncertainty in planning, to encourage the inclusion of mobile broadband in infrastructure rollout, and to facilitate more local and regional involvement in planning and funding are likely to improve longer term outcomes.
Keywords: 330; broadband; availability; regional; Australia